Perancanagan Sistem Informasi Penilaian Mahasiswa Universitas Nahdlatul Ulama Sumatera Barat Berbasis Web - Rizki Amelia, indah; Saputra, Roni (Jurnal TEFSIN ( Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Student assessment at the Nahdlatul Ulama University of West Sumatra is currently still manual, so a lot of time and energy is needed to do this task. the purpose of this thesis is to develop a computerized student assessment information system. in processing data and information will succeed with better changes to the existing system. The Student Assessment Information System is the one whose handling is in accordance with the courses taught by the students. processing of this value includes semester exams conducted by students. this website also contains data collection needed for value processing, namely data collection for students, lecturers, majors, courses, and classes. In addition, as a web-based and online system, this system can be accessed anytime and online using internet access. So that the information submitted is not limited by region and time. This website was developed using the PHP (Personal Home Page) programming language and MySQL database that can be used in various computer operating systems.